Human resource management current directions and new challenges : with overview of international HRM - Mendoza, Ernesto H.; Garcia, Lorma S.P. (Manila Unlimited Books Library Services and Publishing, 2019)
Human resources management is the strategic and coherent approach to their valued assets, it's people. This book is designed to contribute in a modest way, more insights in the field of managing people.

The book also has an updated presentation by inclusion of a Part 2 which is an overview of International Human Resource Management (IHRM). IHRM is the key for MNCs to respond to the impact of globalization on human resource management worldwide.

Theories, concepts and principles are linked with real-life situations on the ground. This was done through activities and varied exercises which were based from the actual corporate experiences of the authors.
Introduction to HRM. -- Job analysis and job design. -- Recruitment: attracting the right talent. -- Selection, placement, and job fit. -- Performance management. -- The value of training and development. -- Compensation and incentives. -- Benefits and benefit administration. -- Globalization and the future of HRM. -- International human resource management (IHRM): an overview
Includes bibliographical references
Keywords: Personnel management; Personnel management -- Forecasting; Diversity in the workplace; Glocalization